Analysis of Marketing Strategy and Break-Even Points of Cassava Leaf Chips for MSMEs in Alaspandan - Aliph Erwansyah; Mochammad Ilyas Junjunan (Jurnal Pengabdian Masyarakat Al-Fatimah, 2024)
Micro and medium-sized enterprises are important in driving the local economy, especially in rural areas such as Alaspandan Village, which has natural potential in cassava leaves. Processing cassava leaves into chips produces added value and opens up employment opportunities for the local community. This study analyzes the marketing strategy and calculation of the Break-Even Point (BEP) in the "Alspand" cassava leaf chips MSME in Alaspandan Village, Pakuniran District, Probolinggo. Using qualitative methods and descriptive analysis, data were obtained through interviews and direct observation of the production and marketing processes. The study results indicate that marketing strategies based on marketing mixes including distribution, price, promotion, and products still need improvement. The use of social media is recommended to expand promotions. Meanwhile, the BEP calculation shows that MSMEs must sell 275 kg of chips or achieve a sales value of IDR.3.055.555 to reach the break-even point. These results serve as a reference for MSMEs in developing effective pricing and marketing strategies to increase sales and profitability. This study contributes by guiding MSMEs in making strategic decisions that are oriented toward sustainable business development